Preparation process of efficient crystalline silicon solar cell
By preparing boron diffusion layer, tunneling oxide layer, MoOx film, vanadium nitride film and doped anti-reflection film in crystalline silicon solar cells, the problem of low light absorption efficiency of crystalline silicon solar cells is solved, and the photoelectric conversion efficiency is improved and the effect of short circuit current density.
Patent Information
- Application Number
- CN202411751460.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The light absorption efficiency and photoelectric conversion efficiency of crystalline silicon solar cells are low, especially the ultraviolet light energy with a wavelength of less than 400nm cannot be effectively converted into electrical energy, resulting in energy loss.
An efficient preparation process is adopted, including the preparation of boron diffusion layer, tunneling oxide layer, polysilicon layer, MoOx film, vanadium nitride film and doped anti-reflection film, these layers are formed through vacuum evaporation and magnetron sputtering technology, using two The solid powder of the meta-complex forms a doped anti-reflective film to improve light absorption and electrical conversion efficiency.
The light absorption efficiency and photoelectric conversion efficiency of crystalline silicon solar cells are improved, the short-circuit current density and filling factor are enhanced, the carrier recombination loss is reduced, and the overall performance of the battery is improved.
Smart Images

Figure CN119300531A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a preparation process of a high-efficiency crystalline silicon solar cell. Background Art
[0002] Crystalline silicon solar cells are photovoltaic devices based on crystalline silicon materials. They generate electric current by converting the energy of photons in sunlight into electron energy, thereby directly converting the energy of sunlight into electrical energy. It is one of the most common and mature types of solar cells and dominates commercial applications.
[0003] However, most of the sunlight energy incident on the surface of crystalline silicon solar cells is dissipated due to lattice thermal vibration loss and transmission loss, and only a small part is absorbed and converted into electrical energy. At present, the photon energy of ultraviolet light with a wavelength within 400nm is much larger than the bandgap width of silicon. Only a small part is effectively converted into electrical energy by silicon solar cells, and the rest is converted into lattice thermal vibration and lost, resulting in relatively low light absorption efficiency and photoelectric conversion efficiency of solar cells.
[0004] Therefore, it is necessary to propose a preparation process for a high-efficiency crystalline silicon solar cell that can improve light absorption efficiency in order to improve its photoelectric conversion efficiency. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a process for preparing a high-efficiency crystalline silicon solar cell.
[0006] A process for preparing a high-efficiency crystalline silicon solar cell comprises the following steps: S1: Texturing and front boron diffusion The N-type crystalline silicon wafer is cleaned and textured, and then a boron diffusion layer is formed on the front side using a boron-containing doping source, and the borosilicate glass diffused to the back side is removed with an acid solution to obtain a boron diffusion layer silicon wafer; S2: Preparation of tunnel oxide layer and polysilicon layer A tunnel oxide layer with a thickness of 4-6 nm is prepared on the back of the boron diffusion layer silicon wafer by LPCVD, and then a polysilicon layer with a thickness of 80-100 nm is deposited on the tunnel oxide layer. Then, an acid solution is used to remove the polysilicon and phosphosilicate glass diffused to the front side, and high-temperature annealing is performed. Finally, an acid solution is used to remove the phosphosilicate glass layer on the back side and the borosilicate glass layer on the front side to obtain a back TOPCon structure silicon wafer. S3: Preparation of double-layer coated silicon wafers MoO was thermally evaporated on the back side of the TOPCon structured silicon wafer. x film, then in MoO x A vanadium nitride film is deposited on the surface of the film to obtain a double-layer coated silicon wafer; S4: Preparation of binary complex solid powder Dissolving europium oxide and lanthanum oxide in concentrated hydrochloric acid to prepare a mixed chloride solid, then dissolving the mixed chloride solid in ethanol to prepare a mixed chloride solution for standby use, then dissolving dibenzoylmethane in ethanol, adding the mixed chloride solution, heating and stirring to form a complex, and finally adding an ethanol solution of tetradecanoic acid and an ethanol solution of o-phenanthroline in sequence to react to obtain a binary complex solid powder; S5: Preparation of doped anti-reflection film The ethyl orthosilicate, anhydrous ethanol and deionized water are mixed to form a mixed solution, hydrochloric acid is added to adjust the pH, and the solution is heated and stirred to form a silica sol, and then the above binary complex solid powder is added, stirred and dispersed, and allowed to stand for aging to form a mixed sol, and finally the double-layer coated silicon wafer is immersed in the mixed sol, and a coating is performed by pulling, and after heat treatment, a doped anti-reflection film layer is formed to obtain a passivated silicon wafer; S6: Preparation of metal electrodes Metal electrodes are prepared on the front and back sides of the passivated silicon wafer to obtain a crystalline silicon solar cell.
[0007] Furthermore, S3 specifically includes the following steps: S3.1: Move the back TOPCon structure silicon wafer obtained in step S2 into the vacuum evaporation coating equipment and adjust the vacuum degree to (4-5)×10 -4 Pa, a layer of MoO with a thickness of 20-30nm is thermally evaporated on the back side. x Film, to obtain a single-layer coated silicon wafer; S3.2: Using pure vanadium as target material, argon as sputtering gas and ammonia as reaction gas, a layer of vanadium nitride film is deposited on the back of the above-mentioned single-layer coated silicon wafer by magnetron sputtering, and then annealed at a high temperature of 200-300°C to obtain a double-layer coated silicon wafer.
[0008] Furthermore, S4 specifically includes the following steps: S4.1: Dissolve europium oxide and lanthanum oxide in concentrated hydrochloric acid at a solid-liquid ratio of (2-3) g:1 g:(20-30) mL, heating and stirring until evaporated to dryness to obtain a mixed chloride solid; S4.2: Add the above mixed chloride solid into ethanol at a solid-liquid ratio of 1 g: (40-50) mL, stir thoroughly to dissolve, and obtain a mixed chloride solution; S4.3: Add dibenzoylmethane to ethanol at a solid-liquid ratio of 1 g: (20-30) mL, stir thoroughly to dissolve, then add the above mixed chloride solution, continue stirring to mix, then add ammonia water to adjust the pH to 6-7, and heat and stir at 50-60°C for 1-2 hours to form a complex to obtain suspension A; S4.4: Dissolve tetradecanoic acid in ethanol at a solid-liquid ratio of 1 g: (50-60) mL, add the mixture to the suspension A, adjust the pH to 6-7 with aqueous ammonia, keep the temperature constant, and continue stirring the reaction for 40-50 min to obtain a suspension B; S4.5: Dissolve o-phenanthroline in ethanol at a solid-liquid ratio of 1g: (60-70)mL, and add it to the above suspension B. Adjust the pH to 6-7 with aqueous ammonia. Keep the temperature unchanged, continue stirring the reaction for 1-2h, let it stand for 8-10h, filter, wash and vacuum dry to obtain a binary complex solid powder.
[0009] Furthermore, S5 specifically includes the following steps: S5.1: mix tetraethyl orthosilicate, anhydrous ethanol and deionized water in a molar ratio of 1:(10-16):(4-6) to prepare a mixed solution; S5.2: Add hydrochloric acid to the mixed solution to adjust the pH to 3-4, then heat and stir at 50-60° C. for 1-2 h, and cool naturally to room temperature to obtain silica sol; S5.3: Add the binary complex solid powder obtained in step S4.5 to the above-mentioned silica sol, stir and disperse them thoroughly, and then let them stand for 28-32 hours to obtain a mixed sol; S5.4: Immerse the double-layer coated silicon wafer obtained in step S3.2 in the above-mentioned mixed sol, let it stand for 2-3 minutes, pull up the coating at a speed of 1500-2000μm / s, and after heat treatment at 200-300℃ for 30-40min, form a doped anti-reflection passivation film layer on the front and back sides of the double-layer coated silicon wafer to obtain a passivated silicon wafer.
[0010] Furthermore, the evaporation rate of the vacuum evaporation coating equipment is 0.3-0.5Å / s.
[0011] Furthermore, the magnetron sputtering conditions are as follows: argon flow rate is 40-50 sccm, ammonia flow rate is 60-80 sccm, sputtering power is 180-220 W, deposition pressure is 0.6-0.8 Pa, and sputtering time is 1-2 h.
[0012] Furthermore, the molar ratio of dibenzoylmethane to europium chloride in the mixed chloride solution is (2-3):1.
[0013] Furthermore, the volume ratio of the tetradecanoic acid ethanol solution to the suspension A is 1:(1.4-1.6).
[0014] Furthermore, the volume ratio of the ethanol solution of o-phenanthroline to the suspension B is 1:(1.8-2.4).
[0015] Furthermore, the amount of the binary complex solid powder added is 0.3-0.5% of the mass of the silica sol.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention comprises the following steps: firstly dissolving europium oxide in concentrated hydrochloric acid to prepare a mixed chloride, then dissolving the mixed chloride in ethanol, adding the mixed chloride to an ethanol solution of dibenzoylmethane, heating and stirring to form a complex, then adding an ethanol solution of tetradecanoic acid, heating and stirring to react, then adding an ethanol solution of o-phenanthroline, continuing heating and stirring to react, preparing a binary complex solid powder, adding the binary complex solid powder to a silica sol, and performing Czochralski coating on a double-layer coated silicon wafer, and after a doped anti-reflection passivation film is formed on the front and back surfaces thereof, on the one hand, since the amount of the binary complex solid powder added is small, the visible light transmittance of the anti-reflection film will not be reduced, and on the other hand, the binary complex The europium ions in the solid powder can enable the doped anti-reflection passivation film to convert ultraviolet light that is not easily absorbed by crystalline silicon solar cells into visible light with good spectral response, thereby improving the light absorption efficiency of solar cells and achieving the effect of improving the conversion efficiency of crystalline silicon solar cells. In addition, since the lanthanum ion itself does not emit light, its 4f electrons are generally half-filled or fully filled, and its lowest excited state energy level is much higher than the excited triplet state energy level of the ligand. The ligand cannot effectively give energy to the lanthanum ion, resulting in the energy being concentratedly transferred to the europium ion. Therefore, the introduction of the lanthanum element can cooperate with the europium ion to further enhance the luminescence intensity of the doped anti-reflection passivation film, so that the photoelectric conversion efficiency of the battery is further improved.
[0017] 2. The present invention uses a vacuum evaporation coating device to thermally evaporate a layer of MoO on the back of the TOPCon structure silicon wafer. x On the one hand, due to the MoO x The film has a high hole mobility, which can effectively transport holes and reduce the recombination loss of holes, thereby increasing the short-circuit current density of crystalline silicon solar cells. On the other hand, MoO x The film can also provide a certain interface passivation effect, reduce the surface state density, and increase the carrier lifetime, thereby increasing the fill factor of crystalline silicon solar cells.
[0018] 3. The present invention uses pure vanadium as the target material and ammonia as the reaction gas to deposit MoO on the back by magnetron sputtering. x A vanadium nitride film is deposited on the back of the single-layer coated silicon wafer of the membrane layer to realize the collection of carrier holes. Since vanadium nitride can selectively transmit holes and reduce the transmission of electrons, it helps to reduce the recombination loss of carriers at the interface, improve the hole collection efficiency, and help the holes to be quickly transmitted to the electrode, thereby achieving the purpose of improving the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0020] Figure 1 This is a process flow chart for preparing a high-efficiency crystalline silicon solar cell used in an embodiment of the present invention. DETAILED DESCRIPTION
[0021] The following is a detailed description of a preparation process of a high-efficiency crystalline silicon solar cell provided by the present invention through specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.
[0022] Example 1 A process for preparing a high-efficiency crystalline silicon solar cell comprises the following steps: S1: Texturing and front boron diffusion The N-type crystalline silicon wafer is cleaned and textured, and then a boron diffusion layer is formed on the front side using a boron-containing doping source, and the borosilicate glass diffused to the back side is removed with an acid solution to obtain a boron diffusion layer silicon wafer; S2: Preparation of tunnel oxide layer and polysilicon layer A 4nm thick tunnel oxide layer is prepared on the back of the boron diffusion layer silicon wafer by LPCVD, and then a 80nm thick polysilicon layer is deposited on the tunnel oxide layer. Then, the polysilicon and phosphosilicate glass diffused to the front are removed by acid solution, and high temperature annealing is performed. Finally, the phosphosilicate glass layer on the back and the borosilicate glass layer on the front are removed by acid solution to obtain a back TOPCon structure silicon wafer. S3: Preparation of double-layer coated silicon wafers The back TOPCon structure silicon wafer prepared in step S2 was moved into the vacuum evaporation coating equipment and the vacuum degree was adjusted to 4×10 -4 Pa, a 20 nm thick MoO layer was thermally evaporated on the back side at an evaporation rate of 0.3 Å / s. x A single-layer coated silicon wafer is obtained by forming a film, and then a layer of vanadium nitride film is deposited on the back of the single-layer coated silicon wafer by magnetron sputtering using pure vanadium as a target, argon as a sputtering gas, and ammonia as a reaction gas. After high-temperature annealing at 200°C, a double-layer coated silicon wafer is obtained, wherein the magnetron sputtering conditions are as follows: argon flow rate is 40sccm, ammonia flow rate is 60sccm, sputtering power is 180W, deposition pressure is 0.6Pa, and sputtering time is 1h; S4: Preparation of binary complex solid powder Europium oxide and lanthanum oxide were dissolved in concentrated hydrochloric acid at a solid-liquid ratio of 2g:1g:20mL, and the mixture was heated and stirred until evaporated to dryness to obtain a mixed chloride solid. Subsequently, the mixed chloride solid was added to ethanol at a solid-liquid ratio of 1g:40mL, and the mixture was fully stirred and dissolved to obtain a mixed chloride solution. Then, dibenzoylmethane was added to ethanol at a solid-liquid ratio of 1g:20mL, and the mixture was fully stirred and dissolved. Then, the mixed chloride solution was added, and the stirring and mixing were continued. Then, ammonia water was added to adjust the pH to 6, and the mixture was heated and stirred at 50°C for 1h to form a complex to obtain a suspension A, wherein the molar ratio of dibenzoylmethane to europium chloride in the mixed chloride solution was 2:1 Then, tetradecanoic acid was dissolved in ethanol at a solid-liquid ratio of 1g:50mL, and then added to suspension A, and the pH was adjusted to 6 with ammonia water, the temperature was kept constant, and the reaction was continued with stirring for 40min to obtain suspension B, wherein the volume ratio of the tetradecanoic acid ethanol solution to the suspension A was 1:1.4, and finally, o-phenanthroline was dissolved in ethanol at a solid-liquid ratio of 1g:60mL, and then added to suspension B, and the pH was adjusted to 6 with ammonia water, the temperature was kept constant, the reaction was continued with stirring for 1h, and the mixture was allowed to stand for 8h, and then filtered, washed and vacuum dried to obtain a binary complex solid powder, wherein the volume ratio of the o-phenanthroline ethanol solution to the suspension B was 1:1.8; S5: Preparation of doped anti-reflection film TEOS, anhydrous ethanol and deionized water are stirred and mixed in a molar ratio of 1:10:4 to prepare a mixed solution, and then hydrochloric acid is added to the mixed solution to adjust the pH to 3, and then heated and stirred at 50°C for 1 hour, and naturally cooled to room temperature to obtain a silica sol, and then the above binary complex solid powder is added to the silica sol, fully stirred and dispersed, and then allowed to stand for 28 hours to obtain a mixed sol, wherein the amount of the binary complex solid powder added is 0.3% of the mass of the silica sol, and then the double-layer coated silicon wafer is immersed in the above mixed sol, and after standing for 2 minutes, the coating is pulled at a speed of 1500 μm / s, and after heat treatment at 200°C for 30 minutes, a doped anti-reflection passivation film layer is formed on the front and back sides of the double-layer coated silicon wafer to obtain a passivated silicon wafer; S6: Preparation of metal electrodes Metal electrodes are prepared on the front and back sides of the passivated silicon wafer to obtain a crystalline silicon solar cell.
[0023] Example 2 A process for preparing a high-efficiency crystalline silicon solar cell comprises the following steps: S1: Texturing and front boron diffusion The N-type crystalline silicon wafer is cleaned and textured, and then a boron diffusion layer is formed on the front side using a boron-containing doping source, and the borosilicate glass diffused to the back side is removed with an acid solution to obtain a boron diffusion layer silicon wafer; S2: Preparation of tunnel oxide layer and polysilicon layer A 5nm thick tunnel oxide layer is prepared on the back of the boron diffusion layer silicon wafer by LPCVD, and then a 90nm thick polysilicon layer is deposited on the tunnel oxide layer. Then, the polysilicon and phosphosilicate glass diffused to the front are removed by acid solution, and high temperature annealing is performed. Finally, the phosphosilicate glass layer on the back and the borosilicate glass layer on the front are removed by acid solution to obtain a back TOPCon structure silicon wafer. S3: Preparation of double-layer coated silicon wafers The back TOPCon structure silicon wafer prepared in step S2 was moved into the vacuum evaporation coating equipment and the vacuum degree was adjusted to 4×10 -4 Pa, a 25 nm thick MoO layer was thermally evaporated on the back side at an evaporation rate of 0.4 Å / s. x A single-layer coated silicon wafer is obtained by forming a film, and then a layer of vanadium nitride film is deposited on the back of the single-layer coated silicon wafer by magnetron sputtering using pure vanadium as a target, argon as a sputtering gas, and ammonia as a reaction gas. After high-temperature annealing at 250°C, a double-layer coated silicon wafer is obtained, wherein the magnetron sputtering conditions are as follows: argon flow rate is 45sccm, ammonia flow rate is 70sccm, sputtering power is 200W, deposition pressure is 0.7Pa, and sputtering time is 1.5h; S4: Preparation of binary complex solid powder Europium oxide and lanthanum oxide were dissolved in concentrated hydrochloric acid at a solid-liquid ratio of 2.5 g:1 g:25 mL, and the mixture was heated and stirred until evaporated to dryness to obtain a mixed chloride solid. Subsequently, the mixed chloride solid was added to ethanol at a solid-liquid ratio of 1 g:45 mL, and the mixture was fully stirred to dissolve to obtain a mixed chloride solution. Then, dibenzoylmethane was added to ethanol at a solid-liquid ratio of 1 g:25 mL, and the mixture was fully stirred to dissolve. Then, the mixed chloride solution was added, and the stirring and mixing were continued. Then, ammonia water was added to adjust the pH to 6.5, and the mixture was heated and stirred at 55° C. for 1.5 hours to form a complex to obtain a suspension A, wherein the molar ratio of dibenzoylmethane to europium chloride in the mixed chloride solution was 2.5: 1. Subsequently, tetradecanoic acid was dissolved in ethanol at a solid-liquid ratio of 1g:55mL, and then added to suspension A, and the pH was adjusted to 6.5 with ammonia water, the temperature was kept constant, and the reaction was continued with stirring for 45min to obtain suspension B, wherein the volume ratio of the tetradecanoic acid ethanol solution to the suspension A was 1:1.5. Finally, o-phenanthroline was dissolved in ethanol at a solid-liquid ratio of 1g:65mL, and then added to suspension B, and the pH was adjusted to 6.5 with ammonia water, the temperature was kept constant, the reaction was continued with stirring for 1.5h, and the mixture was allowed to stand for 9h. After filtering, washing and vacuum drying, a binary complex solid powder was obtained, wherein the volume ratio of the o-phenanthroline ethanol solution to the suspension B was 1:2.1; S5: Preparation of doped anti-reflection film TEOS, anhydrous ethanol and deionized water are stirred and mixed in a molar ratio of 1:13:5 to prepare a mixed solution, and then hydrochloric acid is added to the mixed solution to adjust the pH to 3.5, and then heated and stirred at 55°C for 1.5 hours, and naturally cooled to room temperature to obtain a silica sol, and then the above binary complex solid powder is added to the silica sol, fully stirred and dispersed, and then allowed to stand for aging for 30 hours to obtain a mixed sol, wherein the amount of the binary complex solid powder added is 0.4% of the mass of the silica sol, and then the double-layer coated silicon wafer is immersed in the above mixed sol, and after standing for 2.5 minutes, the coating is pulled at a speed of 1750 μm / s, and after heat treatment at 250°C for 35 minutes, a doped anti-reflection passivation film layer is formed on the front and back sides of the double-layer coated silicon wafer, respectively, to obtain a passivated silicon wafer; S6: Preparation of metal electrodes Metal electrodes are prepared on the front and back sides of the passivated silicon wafer to obtain a crystalline silicon solar cell.
[0024] Example 3 A process for preparing a high-efficiency crystalline silicon solar cell comprises the following steps: S1: Texturing and front boron diffusion The N-type crystalline silicon wafer is cleaned and textured, and then a boron diffusion layer is formed on the front side using a boron-containing doping source, and the borosilicate glass diffused to the back side is removed with an acid solution to obtain a boron diffusion layer silicon wafer; S2: Preparation of tunnel oxide layer and polysilicon layer A 6nm thick tunnel oxide layer is prepared on the back of the boron diffusion layer silicon wafer by LPCVD, and then a 100nm thick polysilicon layer is deposited on the tunnel oxide layer. Then, the polysilicon and phosphosilicate glass diffused to the front are removed by acid solution, and high temperature annealing is performed. Finally, the phosphosilicate glass layer on the back and the borosilicate glass layer on the front are removed by acid solution to obtain a back TOPCon structure silicon wafer. S3: Preparation of double-layer coated silicon wafers The back TOPCon structure silicon wafer prepared in step S2 was moved into the vacuum evaporation coating equipment and the vacuum degree was adjusted to 5×10 -4 Pa, a 30nm thick MoO layer was thermally evaporated on the back side at an evaporation rate of 0.5Å / s. x A single-layer coated silicon wafer is obtained by forming a film, and then a layer of vanadium nitride film is deposited on the back of the single-layer coated silicon wafer by magnetron sputtering using pure vanadium as a target, argon as a sputtering gas, and ammonia as a reaction gas. After high-temperature annealing at 300°C, a double-layer coated silicon wafer is obtained, wherein the magnetron sputtering conditions are as follows: argon flow rate is 50sccm, ammonia flow rate is 80sccm, sputtering power is 220W, deposition pressure is 0.8Pa, and sputtering time is 2h; S4: Preparation of binary complex solid powder Europium oxide and lanthanum oxide were dissolved in concentrated hydrochloric acid at a solid-liquid ratio of 3g:1g:30mL, and the mixture was heated and stirred until evaporated to dryness to obtain a mixed chloride solid. Subsequently, the mixed chloride solid was added to ethanol at a solid-liquid ratio of 1g:50mL, and the mixture was fully stirred and dissolved to obtain a mixed chloride solution. Then, dibenzoylmethane was added to ethanol at a solid-liquid ratio of 1g:30mL, and the mixture was fully stirred and dissolved. Then, the mixed chloride solution was added, and the stirring and mixing were continued. Then, ammonia water was added to adjust the pH to 7, and the mixture was heated and stirred at 60°C for 2h to form a complex to obtain a suspension A, wherein the molar ratio of dibenzoylmethane to europium chloride in the mixed chloride solution was 3:1 Then, tetradecanoic acid was dissolved in ethanol at a solid-liquid ratio of 1g:60mL, and then added to suspension A, and the pH was adjusted to 7 with ammonia water, the temperature was kept constant, and the reaction was continued with stirring for 50min to obtain suspension B, wherein the volume ratio of the tetradecanoic acid ethanol solution to the suspension A was 1:1.6, and finally, o-phenanthroline was dissolved in ethanol at a solid-liquid ratio of 1g:70mL, and then added to suspension B, and the pH was adjusted to 7 with ammonia water, the temperature was kept constant, the reaction was continued with stirring for 2h, and the mixture was allowed to stand for 10h, filtered, washed and vacuum dried to obtain a binary complex solid powder, wherein the volume ratio of the o-phenanthroline ethanol solution to the suspension B was 1:2.4; S5: Preparation of doped anti-reflection film TEOS, anhydrous ethanol and deionized water are stirred and mixed in a molar ratio of 1:16:6 to prepare a mixed solution, and then hydrochloric acid is added to the mixed solution to adjust the pH to 4, and then heated and stirred at 60°C for 2 hours, and naturally cooled to room temperature to obtain a silica sol, and then the above binary complex solid powder is added to the silica sol, fully stirred and dispersed, and then allowed to stand for aging for 32 hours to obtain a mixed sol, wherein the amount of the binary complex solid powder added is 0.5% of the mass of the silica sol, and then the double-layer coated silicon wafer is immersed in the above mixed sol, and after standing for 3 minutes, the coating is pulled at a speed of 2000 μm / s, and after heat treatment at 300°C for 40 minutes, a doped anti-reflection passivation film layer is formed on the front and back sides of the double-layer coated silicon wafer, respectively, to obtain a passivated silicon wafer; S6: Preparation of metal electrodes Metal electrodes are prepared on the front and back sides of the passivated silicon wafer to obtain a crystalline silicon solar cell.
[0025] Comparative Example 1 The difference from Example 1 is that step S4 is removed, and the binary complex solid powder in step S5 is removed.
[0026] Comparative Example 2 The difference from Example 1 is that the lanthanum oxide in step S4 is replaced by an equal amount of europium oxide.
[0027] Comparative Example 3 The only difference from Example 1 is that the vacuum thermal evaporation of MoO in step S3 is x The film is removed in the step, and a layer of vanadium nitride film is magnetron sputtered directly on the back side of the TOPCon structure silicon wafer.
[0028] Comparative Example 4 The difference from Example 1 is that the magnetron sputtering step of the vanadium nitride film in step S3 is removed, and the doped anti-reflection film layer is directly prepared on the surface of the single-layer coated silicon wafer.
[0029] Performance Testing Test 1: The average optical transmittance of the doped anti-reflection films prepared in Examples 1-3 and the anti-reflection film prepared in Comparative Example 1 without adding the binary complex solid powder was tested and calculated using an ultraviolet visible spectrophotometer (UV3600Plus) in the range of 400-1100nm. The results are shown in Table 1.
[0030] Table 1: Comparison of average optical transmittance of Examples 1-3 and Comparative Example 1 Test 2: The photoelectric properties of Examples 1-3 and Comparative Example 1 were tested using a solar energy test system at AM 1.5 and 25°C. The results are shown in Table 2.
[0031] Table 2: Comparison of photoelectric properties of Examples 1-3 and Comparative Examples 1-3 First, it can be seen from Table 1 that the optical transmittance of the anti-reflection film prepared in Comparative Example 1 without adding the binary complex solid powder is almost the same as that of the doped anti-reflection film prepared in Example 1 with adding the binary complex solid powder, while it can be seen from Table 2 that the photoelectric conversion efficiency of the crystalline silicon solar cell prepared in Comparative Example 1 is significantly lower than that in Example 1. It can be seen that by first dissolving europium oxide in concentrated hydrochloric acid to prepare a mixed chloride, then dissolving the mixed chloride in ethanol, adding it to an ethanol solution of dibenzoylmethane, heating and stirring to form a complex, then adding an ethanol solution of tetradecanoic acid, heating and stirring to react, and then adding an ethanol solution of o-phenanthroline , continue heating and stirring to react, prepare a binary complex solid powder, add the binary complex solid powder into the silica sol, and pull and coat the double-layer coated silicon wafer, after the doped anti-reflection passivation film is formed on the front and back surfaces thereof, on the one hand, due to the small amount of the binary complex solid powder added, the visible light transmittance of the anti-reflection film will not decrease, and on the other hand, the europium ions in the binary complex solid powder can enable the doped anti-reflection passivation film to convert the ultraviolet light that is not easily absorbed by the crystalline silicon solar cell into visible light with good spectral response, thereby improving the light absorption efficiency of the solar cell, and achieving the effect of improving the conversion efficiency of the crystalline silicon solar cell; In addition, after replacing lanthanum oxide with europium oxide in Comparative Example 2, the photoelectric conversion efficiency of the obtained crystalline silicon solar cell is lower than that in Example 1. It can be seen that since the lanthanum ion itself does not emit light, its 4f electrons are generally half-filled or fully filled, and its lowest excited state energy level is much higher than the excited triplet energy level of the ligand. The ligand cannot effectively give energy to the lanthanum ion, resulting in the energy being concentrated and transferred to the europium ion. Therefore, the introduction of lanthanum elements can cooperate with europium ions to further enhance the luminescence intensity of the doped anti-reflective passivation film, thereby further improving the photoelectric conversion efficiency of the battery.
[0032] Secondly, it can be seen from Table 2 that in Comparative Example 3, MoO x The photoelectric conversion efficiency of the crystalline silicon solar cell prepared by directly sputtering a layer of vanadium nitride film on the back of the TOPCon structure silicon wafer is about 22.25%, which is lower than that of Example 1. It can be seen that by using a vacuum evaporation coating equipment to thermally evaporate a layer of MoO2 on the back of the TOPCon structure silicon wafer, the photoelectric conversion efficiency of the crystalline silicon solar cell prepared is about 22.25%, which is lower than that of Example 1. x On the one hand, due to the MoO x The film has a high hole mobility, which can effectively transport holes and reduce the recombination loss of holes, thereby increasing the short-circuit current density of crystalline silicon solar cells. On the other hand, MoO x The film can also provide a certain interface passivation effect, reduce the surface state density, and increase the carrier lifetime, thereby increasing the fill factor of crystalline silicon solar cells. x The presence of the film can effectively improve the photoelectric conversion efficiency of the prepared crystalline silicon solar cell.
[0033] Finally, it can be seen from Table 2 that in Comparative Example 4, no vanadium nitride film is prepared, and a doped anti-reflection film layer is directly prepared on the surface of a single-layer coated silicon wafer. The photoelectric conversion efficiency of the prepared crystalline silicon solar cell is about 22.67%, which is lower than that of Example 1. It can be seen that when pure vanadium is used as a target material and ammonia is used as a reaction gas, MoO2 is evaporated on the back surface by magnetron sputtering. x A vanadium nitride film is deposited on the back of the single-layer coated silicon wafer of the membrane layer to realize the collection of carrier holes. Since vanadium nitride can selectively transmit holes and reduce the transmission of electrons, it helps to reduce the recombination loss of carriers at the interface, improve the hole collection efficiency, and help the holes to be quickly transmitted to the electrode, thereby achieving the purpose of improving the photoelectric conversion efficiency.
[0034] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a high-efficiency crystalline silicon solar cell, characterized in that: The steps include: S1: Texturing and front boron diffusion The N-type crystalline silicon wafer is cleaned and textured, and then a boron diffusion layer is formed on the front side using a boron-containing doping source, and the borosilicate glass diffused to the back side is removed with an acid solution to obtain a boron diffusion layer silicon wafer; S2: Preparation of tunnel oxide layer and polysilicon layer A tunnel oxide layer with a thickness of 4-6 nm is prepared on the back of the boron diffusion layer silicon wafer by LPCVD, and then a polysilicon layer with a thickness of 80-100 nm is deposited on the tunnel oxide layer. Then, an acid solution is used to remove the polysilicon and phosphosilicate glass diffused to the front side, and high-temperature annealing is performed. Finally, an acid solution is used to remove the phosphosilicate glass layer on the back side and the borosilicate glass layer on the front side to obtain a back TOPCon structure silicon wafer. S3: Preparation of double-layer coated silicon wafers MoO was thermally evaporated on the back side of the TOPCon structured silicon wafer. x film, then in MoO x A vanadium nitride film is deposited on the surface of the film to obtain a double-layer coated silicon wafer; S4: Preparation of binary complex solid powder Dissolving europium oxide and lanthanum oxide in concentrated hydrochloric acid to prepare a mixed chloride solid, then dissolving the mixed chloride solid in ethanol to prepare a mixed chloride solution for standby use, then dissolving dibenzoylmethane in ethanol, adding the mixed chloride solution, heating and stirring to form a complex, and finally adding an ethanol solution of tetradecanoic acid and an ethanol solution of o-phenanthroline in sequence to react to obtain a binary complex solid powder; S5: Preparation of doped anti-reflection film The ethyl orthosilicate, anhydrous ethanol and deionized water are mixed to form a mixed solution, hydrochloric acid is added to adjust the pH, and the solution is heated and stirred to form a silica sol, and then the above binary complex solid powder is added, stirred and dispersed, and allowed to stand for aging to form a mixed sol, and finally the double-layer coated silicon wafer is immersed in the mixed sol, and a coating is performed by pulling, and after heat treatment, a doped anti-reflection film layer is formed to obtain a passivated silicon wafer; S6: Preparation of metal electrodes Metal electrodes are prepared on the front and back sides of the passivated silicon wafer to obtain a crystalline silicon solar cell.
2. A process for preparing a high-efficiency crystalline silicon solar cell according to claim 1, characterized in that: S3 specifically includes the following steps: S3.1: Move the back TOPCon structure silicon wafer obtained in step S2 into the vacuum evaporation coating equipment and adjust the vacuum degree to (4-5)×10 -4 Pa, a layer of MoO with a thickness of 20-30nm is thermally evaporated on the back side. x Film, to obtain a single-layer coated silicon wafer; S3.2: Using pure vanadium as target material, argon as sputtering gas and ammonia as reaction gas, a layer of vanadium nitride film is deposited on the back of the above-mentioned single-layer coated silicon wafer by magnetron sputtering, and then annealed at a high temperature of 200-300°C to obtain a double-layer coated silicon wafer.
3. A process for preparing a high-efficiency crystalline silicon solar cell according to claim 2, characterized in that: S4 specifically includes the following steps: S4.1: Dissolve europium oxide and lanthanum oxide in concentrated hydrochloric acid at a solid-liquid ratio of (2-3) g:1 g:(20-30) mL, heating and stirring until evaporated to dryness to obtain a mixed chloride solid; S4.2: Add the above mixed chloride solid into ethanol at a solid-liquid ratio of 1 g: (40-50) mL, stir thoroughly to dissolve, and obtain a mixed chloride solution; S4.3: Add dibenzoylmethane to ethanol at a solid-liquid ratio of 1 g: (20-30) mL, stir thoroughly to dissolve, then add the above mixed chloride solution, continue stirring to mix, then add ammonia water to adjust the pH to 6-7, and heat and stir at 50-60°C for 1-2 hours to form a complex to obtain suspension A; S4.4: Dissolve tetradecanoic acid in ethanol at a solid-liquid ratio of 1 g: (50-60) mL, add the mixture to the suspension A, adjust the pH to 6-7 with aqueous ammonia, keep the temperature constant, and continue stirring the reaction for 40-50 min to obtain a suspension B; S4.5: Dissolve o-phenanthroline in ethanol at a solid-liquid ratio of 1g: (60-70)mL, and add it to the above suspension B. Adjust the pH to 6-7 with aqueous ammonia. Keep the temperature unchanged, continue stirring the reaction for 1-2h, let it stand for 8-10h, filter, wash and vacuum dry to obtain a binary complex solid powder.
4. A process for preparing a high-efficiency crystalline silicon solar cell according to claim 3, characterized in that: S5 specifically includes the following steps: S5.1: mix tetraethyl orthosilicate, anhydrous ethanol and deionized water in a molar ratio of 1:(10-16):(4-6) to prepare a mixed solution; S5.2: Add hydrochloric acid to the mixed solution to adjust the pH to 3-4, then heat and stir at 50-60°C for 1-2h, and cool naturally to room temperature to obtain silica sol; S5.3: Add the binary complex solid powder obtained in step S4.5 to the above-mentioned silica sol, stir and disperse them thoroughly, and then let them stand for 28-32 hours to obtain a mixed sol; S5.4: Immerse the double-layer coated silicon wafer obtained in step S3.2 in the above-mentioned mixed sol, let it stand for 2-3 minutes, pull up the coating at a speed of 1500-2000μm / s, and after heat treatment at 200-300℃ for 30-40min, form a doped anti-reflection passivation film layer on the front and back sides of the double-layer coated silicon wafer to obtain a passivated silicon wafer.
5. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 2, characterized in that: The evaporation rate of vacuum evaporation coating equipment is 0.3-0.5Å / s.
6. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 2, characterized in that: The magnetron sputtering conditions are as follows: argon flow rate is 40-50sccm, ammonia flow rate is 60-80sccm, sputtering power is 180-220W, deposition pressure is 0.6-0.8Pa, and sputtering time is 1-2h.
7. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 3, characterized in that: The molar ratio of dibenzoylmethane to europium chloride in the mixed chloride solution is (2-3):
1.
8. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 3, characterized in that: The volume ratio of the tetradecanoic acid ethanol solution to the suspension A is 1:(1.4-1.6).
9. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 3, characterized in that: The volume ratio of the ethanol solution of o-phenanthroline to the suspension B is 1:(1.8-2.4).
10. The process for preparing a high-efficiency crystalline silicon solar cell according to claim 4, characterized in that: The amount of the binary complex solid powder added is 0.3-0.5% of the mass of the silica sol.
Citation Information
Patent Citations
IBC battery passive film, IBC battery and preparation method thereof
CN109935638A
Solar cell preparing method
CN110311011A
Solar cell with passivation contact and preparation method thereof
CN113644142A
Laminated solar cell and photovoltaic module
CN115768145A
Down-conversion EVA composite adhesive film for photovoltaic module and preparation method of down-conversion EVA composite adhesive film
CN117625066A